The imposition of power through touch: a sensory criminology approach to understanding body searches - Warr, Jason (Body Searches and Imprisonment, 2023)
One of the key principles of Sensory Criminology is that we are embodied creatures who experience the world of criminal justice sensorially. When people are captured within the criminal justice net, those processes are not only experienced via the sensory but, as we set out in Sensory Penalities: Exploring the Senses in Spaces of Punishment and Social Control (Herrity et al., 2021), the principles, intentions, the very ethea, of the criminal justice system are inherently encoded into the sensorial outputs of those practices. Nowhere is this more immediate and apparent than in the searching practices we see within the everyday life of places of incarceration. Every pat down search, every strip search, highlights the enforced, imposed, touch of powerful others on the bodies of those rendered vulnerable. Each and every instance of touch, of unwanted touch, communicates both the power of the state, the carceral institution, and reinforces the profoundly subaltern and helpless position of the prisoner, visitor, exposed other. Acquiescence to this bodily intrusion is demanded. Resistance to this intrusive, power laden, and unwanted touch only invokes further, more invasive, more controlling, touch. To truly understand, and to help the public to understand, the nature of places of incarceration, and the power wielded within them, we need to explore and communicate these visceral impositions. This chapter, utilising both autoethnographic accounts and wider data from a number of research projects in various places of incarceration, will discuss this underexplored facet of the carceral lifeworld.